LTZVisor: TrustZone is the key - Pinto, Sandro (2017)
Virtualization technology starts becoming more and more widespread in the embedded systems arena, driven by the upward trend for integrating multiple environments into the same hardware platform. The penalties incurred by standard software-based virtualization, altogether with the strict timing requirements imposed by real-time virtualization are pushing research towards hardware-assisted solutions. Among existing commercial off-the-shelf (COTS) technologies, ARM TrustZone promises to be a game-changer for virtualization, despite of this technology still being seen with a lot of obscurity and scepticism. In this paper we present a Lightweight TrustZoneassisted Hypervisor (LTZVisor) as a tool to understand, evaluate and discuss the benefits and limitations of using TrustZone hardware to assist virtualization. We demonstrate how TrustZone can be adequately exploited for meeting the real-time needs, while presenting a low performance cost on running unmodified rich operating systems. While ARM continues to spread TrustZone technology from the applications processors to the smallest of microcontrollers, it is undeniable that this technology is gaining an increasing relevance. Our intent is to encourage research and drive the next generation of TrustZone-assisted virtualization solutions.